Phylogenetic analysis of porcine circovirus 2 and its related viruses - Wen, Libin; Wen, Han; Xiao, Qi; Xie, Jianping; He, Kongwang (Frontiers in Veterinary Science, 2025)
IntroductionPorcine circovirus (PCV) belongs to the family Circoviridae. Four conventional PCVs (PCV1 to PCV4) have been discovered over time. PCV1 and PCV2 exhibit higher nucleotide identity compared to PCV3 and PCV4. PCV2, in particular, has caused porcine circovirus-associated diseases (PCVAD), posing a significant threat to the global swine industry. Subsequently, unconventional PCVs, including porcine circovirus-like viruses and porcine circovirus-like mini agents, with genome sequences highly homologous to the PCV2 capsid protein sequence, have been reported.MethodsThis advancement facilitates phylogenetic analysis of these sequences to elucidate the evolutionary history of PCV2, although its true origin remains undetermined.Results and discussionBased on the findings, it is speculated that PCV2 may have originated from ancestral non-coding DNA sequences. This speculation provides new insights into the evolutionary question of which nucleic acid and protein first emerged.